Comparison of Hybrid Diversity and Space Diversity for Microwave Link Between Islands - Mohammad Andri Kurnia; Eka Wahyudi; Solichah Larasati (CESS (Journal of Computer Engineering, System and Science), 2020)
The development of telecommunications technology today, so that some islands are still not affordable from telecommunications technology. The considerable distance between islands requires the efficiency and flexibility of the technology used. The microwave communication system is a technology that is widely implemented as a cellular network backhaul network because it has advantages in the simplicity of installation and can reach remote areas that are difficult to reach. But on the receiving side, the signal received not only comes from the LOS (Line of Sight) signal but the signal is also reflected by the surface of the Earth. The signal from some of these reflections is called multipath, the signal will cause interference that can cause fading or changes in the electromagnetic waves received. To overcome multipath fading that is too high, it is necessary to optimize antenna diversity using hybrid diversity and space diversity techniques. At maximum optimization of hybrid diversity with 135λ and 300 MHz, RSL -34.54 dBm is obtained, the fading margin is 33.70 dB, and availability is 99.99987%, the optimization is better than space diversity at maximum optimization with 135λ. Optimization of hybrid diversity has met ITU-R standards, with RSL values below -30 dBm and availability above 99.900% - 99.9966%, for the value of fading margins still do not meet the standards but can overcome multipath fading problems.